2022
DOI: 10.2147/ijgm.s354842
|View full text |Cite
|
Sign up to set email alerts
|

Value of Serum miRNA-96-5p and miRNA-99a-5p as Diagnostic Biomarkers for Hepatocellular Carcinoma

Abstract: Purpose: Circulatory microRNAs (miRNAs) have the potential to be employed as markers for cancer detection and as prognostic tools for disease management. As a result, our goal was to explore the effectiveness of serum miRNA-96-5p and miRNA-99a-5p as diagnostic tools in hepatocellular carcinoma (HCC). Patients and methods: Blood samples were collected from 55 patients with HCV-induced HCC, 55 patients with HCV-induced liver cirrhosis, and 55 healthy controls. The expression levels of miRNA-96-5p and miRNA-99a-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Most significant decreases were observed in EV-associated miR-451a, miR-374a-5p, miR-96-5p, and miR-16-5p. Of the top ten dysregulated miRNAs, miR-25-3p, miR-96-5p, and miR-30a-5p have been reported as biomarkers for discriminating hepatocellular carcinoma patients (11,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Amongst them, miR-25-3p has been shown to promote hepatocellular carcinoma cell growth, migration, and invasion (54).…”
Section: Discussionmentioning
confidence: 99%
“…Most significant decreases were observed in EV-associated miR-451a, miR-374a-5p, miR-96-5p, and miR-16-5p. Of the top ten dysregulated miRNAs, miR-25-3p, miR-96-5p, and miR-30a-5p have been reported as biomarkers for discriminating hepatocellular carcinoma patients (11,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Amongst them, miR-25-3p has been shown to promote hepatocellular carcinoma cell growth, migration, and invasion (54).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miR-96-5p continually up-regulated in HCC inhibits apoptosis by targeting CASP9. Accordingly, miR-96-5p may be a possible therapeutic target for HCC [ 81 ]. Combined miR-96-5 p with AFP induced sensitivity of HCC detection.…”
Section: Function Of Oncogenic Mirs In Hepatocellular Carcinomamentioning
confidence: 99%
“…In addition, its serum levels were linked to tumor growth and migration. These results suggested that serum miR-96-5p can be used as a non-invasive biomarker for HCC detection [ 81 ].…”
Section: Function Of Oncogenic Mirs In Hepatocellular Carcinomamentioning
confidence: 99%
“…Circulating miRNAs (miRs) have been increasingly recognized as potential biomarkers in cancer [ 25 , 26 ]. Serum levels of miR-141 and miR-200a were decreased in hepatocellular carcinoma and could predict cancer metastasis [ 27 ].…”
Section: Mir-200 Family As a Diagnostic And Prognostic Markermentioning
confidence: 99%